2001
DOI: 10.1089/15246090152563588
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Insufficiency Fractures: A Report of Two Cases and a Review of the Literature

Abstract: Sacral insufficiency fractures (SIF) are a type of stress fracture that occur primarily in postmenopausal women. They were first described in 1982 by Lourie and have since been frequently overlooked as a cause of low back, buttock, or groin pain. We present two cases of SIF to demonstrate the clinical presentation, diagnosis, and treatment of patients with SIF. Both patients were elderly women with complaints of pelvic and low back pain in the absence of significant trauma. Physical examination was significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 35 publications
(38 reference statements)
0
31
0
2
Order By: Relevance
“…4 Fracture-free survival probabilities in the surgical group (red solid line) compared with the nonsurgical group (blue dashed line) are shown. Fracture-free Probability as reported in previous studies, but also can be asymptomatic and we therefore see this as an important limitation [3,7,8,12,18]. Third, six of the 62 patients (all surgical patients) were lost to followup by 2 years, therefore it is possible that the fracture rate in the surgery group is greater than identified in our study.…”
Section: Discussionmentioning
confidence: 58%
“…4 Fracture-free survival probabilities in the surgical group (red solid line) compared with the nonsurgical group (blue dashed line) are shown. Fracture-free Probability as reported in previous studies, but also can be asymptomatic and we therefore see this as an important limitation [3,7,8,12,18]. Third, six of the 62 patients (all surgical patients) were lost to followup by 2 years, therefore it is possible that the fracture rate in the surgery group is greater than identified in our study.…”
Section: Discussionmentioning
confidence: 58%
“…It includes bed rest, analgesic medication and physiotherapy. This management can lead to prolonged pain up to one year and is associated with several complications due to immobilization [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Analgesic effect can be instantaneous, and this benefit, along with improvements in mobility and ability to perform activities of daily living, has been shown to be maintained long term in a small number of cases [6,11,27,30]. With conservative management, patients are often advised that healing will occur over 12 months [20], and admissions for rehabilitation can be prolonged. Dasgupta et al [8] showed that an average stay was 20 days in their hospital when treating conservatively, almost as long as the average in-patient stays following a fractured neck of femur (38 days).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional management has involved analgesia, bed rest and formal rehabilitation. The disadvantages of conservative management can include intractable pain, with significant morbidity and mortality occurring due to periods of prolonged bed rest or impaired mobility [2,20].…”
Section: Introductionmentioning
confidence: 99%